KEBERADAN PT. TORGANDA TERHADAP KEHIDUPAN SOSIAL EKONOMI MASYARAKAT DESA KUALA MAHATO KECAMATAN TAMBUSAI UTARA KABUPATEN ROKAN HULU TAHUN 2005-2015 - Tengku Erdede H; Ridwan Melay; Bedriati Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this study is (1) to find out how the history of the establishment of PT. Torganda Tambusai Utara District, Rokan Hulu Regency in 2005-2015) (2) to find out how the influence of PT. Torganda Against the Social Community of Kuala Mahato Village, North Tambusai District, Rokan Hulu District, 2005-2015. (3) to find out how the influence of PT. Torganda Against the Community Economy of Kuala Mahato Village, North Tambusai Subdistrict, Rokan Hulu Regency 2005-2015. (4) to find out the negative influence of the establishment of PT. Torganda Against the People of Kuala Mahato Village, North Tambusai District, Rokan Hulu District, 2005-2015. (5) To find out about the Corporate Social Responsibility (CSR) program in Kuala Mahato Village, North Tambusai District, Rokan Hulu Regency (2005-2015). In this study using qualitative and comparative-descriptive-analysis methods where this will provide complete information that is beneficial to science. The results of this study that the community in Kuala Mahato, North Tambusai Subdistrict, Riau Province Rokan Hulu Regency in 2005-2015 experienced a development in the socio-economic field which was influenced by the establishment of PT. Torganda with a program of concern for the community where the company is located or in terms of the Corporate Social Responsibility (CSR).Key Words: PT. Torganda desa Kuala Mahato, social-ekonomi